2016
DOI: 10.1021/acsnano.6b02435
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Sculpture of Black Phosphorus Nanoribbons

Abstract: Black phosphorus (BP) is a highly anisotropic allotrope of phosphorus with great promise for fast functional electronics and optoelectronics. We demonstrate the controlled structural modification of few-layer BP along arbitrary crystal directions with sub-nanometer precision for the formation of few-nanometer-wide armchair and zigzag BP nanoribbons. Nanoribbons are fabricated, along with nanopores and nanogaps, using a combination of mechanical–liquid exfoliation and in situ transmission electron microscopy (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
94
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(97 citation statements)
references
References 51 publications
3
94
0
Order By: Relevance
“…Schematics for all of these edges are displayed in Figure 2a from our previous work. 87 During our minimization procedure, we also discovered a number of unreported stable edge reconstructions present in the edges that have yet to be studied independently. Our recent review article on black phosphorus nanostructures discusses other known self-passivating edge configurations that are not present in the antidot geometries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schematics for all of these edges are displayed in Figure 2a from our previous work. 87 During our minimization procedure, we also discovered a number of unreported stable edge reconstructions present in the edges that have yet to be studied independently. Our recent review article on black phosphorus nanostructures discusses other known self-passivating edge configurations that are not present in the antidot geometries.…”
Section: Resultsmentioning
confidence: 99%
“…Such conclusions would require studying the kinetics via transition state tools such as the nudged elastic band method, which has been applied to the edges of phosphorene in other works. 87,88 The energy barrier can then be compared to the thermal energy to determine the probability of a structural transformation. Furthermore, in incrementing to the next largest radius the removed phosphorus atoms do not automatically rearrange into a pristine phosphorene sheet, which is the free energy value that goes into the edge energy calculation.…”
Section: Resultsmentioning
confidence: 99%
“…PNR provides opportunities to use phosphorene in 1D nanoelectronics and to tune the electronic and transport properties of monolayer phosphorene172021. Several studies have shown that the PNR bandgap increases with decreasing ribbon width and that PNR also shows asymmetric conducting behaviour1722; several other properties such as the strain effect, edge saturation, defect, and stability have been studied as well17192022232425.…”
mentioning
confidence: 99%
“…In their work, nanopores on monolayer and few‐layer MoS 2 membranes with variable sizes for DNA sequencing have achieved a high signal‐to‐noise ratio (>10) on detecting four types of nucleotide . The other case is nanopore drilling on BP reported by Das et al The exfoliated few‐layer BP was drilled by the fully focused electron beam with a beam current of 8 nA and a beam diameter of 1 nm (Figure d–f) . This fabrication method is very useful to prepare nanopores made by 2D layered materials due to the following superiorities: a) the superior mechanical, thermal, and chemical characteristics; b) the controlled shape and size fabrication process with nanometer precision.…”
Section: In Situ Tem Manipulation Of 2d Layered Materialsmentioning
confidence: 99%